Forschungsgegenstände und ihre Verwendungsfelder: Exkurse zur Erforschung des Lehrens und Lernens fremder Sprachen II (Brill, 2024)
This volume addresses the issues in inter- and transdisciplinary dialogue as well as the interaction of individual disciplines in handling complex research topics related to foreign language learning and teaching. It is thus a continuation of the volume entitled “Wissenschaften und ihr Dialog. Exkurse zur Erforschung des Lehrens und Lernens fremder Sprachen” (2022). The present volume contains multi-perspective and multi-disciplinary considerations of diverse research objects accounted for from multiple angles of specific disciplines. The contributions confirm that the contemporary research landscape of foreign language learning and teaching involves dealing with complex and multi-faceted phenomena and, accordingly, requires a cross-disciplinary process of reflection as well as multi-perspectivist and collaborative action. They also commit to the meta-subject-specific conceptual reflection on the scientific foundations of foreign language learning and teaching as a research area as well as profiling its content.